Low addition amount of self-healing ionomer binder for Si/graphite electrodes with enhanced cycling. (5th April 2018) - Huang, Shu; Ren, Jianguo; Liu, Rong; Bai, Yang; Li, Xiaolong; Huang, Youyuan; Yue, Min; He, Xueqin; Yuan, Guohui
Abstract : A self-healing ionomer binder is designed and synthesized for commercial Si/graphite anodes (areal capacity of 3 mA h cm −2 ) with a low binder content of 1.8 wt% in Li-ion batteries showing enhanced cycling. Abstract : The commercial application of silicon anodes in Li-ion batteries has been seriously hindered by their poor cycling stability because of their huge volume changes during cycling. In this paper a self-healing ionomer binder, as a crosslinked lithiated polymer, is designed and synthesized for Si/graphite anodes with a low binder content of 1.8 wt%. The self-healing ionomer binder can form hydrogen bonds with Si and graphite particles, which can effectively control the swelling of the electrodes and retain the integrity of the electrodes upon cycling. In addition, Li + in molecule chains can shorten the pathway to the surface of active materials. After cycling, the thickness of the electrodes using a self-healing ionomer binder increases by only about 30%. The self-healing ionomer binder enables enhanced cycling retention and can be used as a significant potential candidate for Si/graphite anodes with a commercial areal capacity of 3 mA h cm −2 .